SOCIAL MAPPING TINGKAT LITERASI INFORMASI MASYARAKAT DESA PASEBAN, KECAMATAN KENCONG, KABUPATEN JEMBER - Domai, Tjahjanulin; Pratiwi, Ratih Nur; V, Niken Lastiti; Widiyawati, Anita Tri (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2017)
Information literacy includes a person's knowledge relating to information needs and the ability to identify, locate, evaluate, process, and create and use information to solve existing problems effectively. The type of research used is survey research with qualitative approach. The result of research indicate that based on IDM value, Paseban Village is classified as developing village with value 0,603. The information literacy level of Paseban villagers is still moderate, that is 62,25% of people understand information access, information evaluation is 52,875% and information usage is 40 , 87%. Potential Paseban village is quite diverse ranging from agriculture, livestock and tourism. Suggested recommendation is Improvement of information literacy of Paseban villagers through training and development of information center that provides access to information for the community. Meanwhile, based on data on village potential and IDM indicator, several recommendations are improvement of water drainage to Sadar times, normalization of irrigation channels, provision of public toilets for coastal areas, agricultural training and tool assistance, greening of mangrov, training of SMEs, establishing cooperatives for fishermen and farmers and improvements village Road.